Cellular Senescence Triggers Altered Circadian Clocks With a Prolonged Period and Delayed Phases - Ahmed, Rezwana; Nakahata, Yasukazu; Shinohara, Kazuyuki; Bessho, Yasumasa (Frontiers in Neuroscience, 2021)
Senescent cells, which show the permanent growth arrest in response to various forms of stress, accumulate in the body with the progression of age and are associated with aging and age-associated diseases. Although the senescent cells are growth arrested, they still demonstrate high metabolic rate and altered gene expressions, indicating that senescent cells are still active. We recently showed that the circadian clock properties, namely phase and period of the cells, are altered with the establishment of replicative senescence. However, whether cellular senescence triggers the alteration of circadian clock properties in the cells is still unknown. In this study we show that the oxidative stress-induced premature senescence induces the alterations of the circadian clock, similar to the phenotypes of the replicative senescent cells. We found that the oxidative stress-induced premature senescent cells display the prolonged period and delayed phases. In addition, the magnitude of these changes intensified over time, indicating that cellular senescence changes the circadian clock properties. Our current results corroborate with our previous findings and further confirm that cellular senescence induces altered circadian clock properties, irrespective of the replicative senescence or the stress-induced premature senescence.